1992
DOI: 10.1021/j100205a054
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the electrocatalytic properties for oxygen reduction of some heat-treated polyacrylonitrile and phthalocyanine cobalt compounds adsorbed on carbon black as probed by electrochemistry and x-ray absorption spectroscopy

Abstract: Electrochemical and X-ray absorption techniques have been used to determine the influence of heat treatment in electrocatalytic activity for O2 reduction for two cobalt catalysts. The catalysts are cobalt phthalocyanine (catalyst 1) and polyacrylonitrile + cobalt acetate (catalyst 2) adsorbed on carbon black and heat treated at several temperatures. A maximum far the catalytic activity was obtained for PcCo at 850 "C and for the PAN + Co catalyst at 950 "C with subsequent decrease. The results obtained by XANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(92 citation statements)
references
References 8 publications
5
87
0
Order By: Relevance
“…The nature of the active site (obtained after heat treatment) in terms of its location on the carbon support (edge versus basal plane) [22], coordination number (Fe-N 4 versus non-Fe-N 4 environment) [23], and chemical identity of the nitrogen functional groups (pyridinic, pyrrolic, and quaternary) [24] have remained a key aspect of intense discussion. Several theories exist to explain the nature of the active site such as those proposed by van Veen et al [25][26][27], McBreen et al [28], Schulenburg et al [29], Yeager et al [2,30], Scherson et al [31][32][33], and Dodelet et al [22,[34][35][36][37][38][39][40][41][42][43][44][45]. Although some authors observed that ORR is conducted by sites comprised of surface nitrogen groups devoid of any metal ion centers [46,47], it is now widely accepted that the transition-metal ion centers coordinated to four nitrogen groups (Me-N 4 ) on graphitic surfaces constitute the active site [22,23,30,48], whereas chelation primarily serves to prevent the metal center from passivation/corrosion under electrochemical conditions [49].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the active site (obtained after heat treatment) in terms of its location on the carbon support (edge versus basal plane) [22], coordination number (Fe-N 4 versus non-Fe-N 4 environment) [23], and chemical identity of the nitrogen functional groups (pyridinic, pyrrolic, and quaternary) [24] have remained a key aspect of intense discussion. Several theories exist to explain the nature of the active site such as those proposed by van Veen et al [25][26][27], McBreen et al [28], Schulenburg et al [29], Yeager et al [2,30], Scherson et al [31][32][33], and Dodelet et al [22,[34][35][36][37][38][39][40][41][42][43][44][45]. Although some authors observed that ORR is conducted by sites comprised of surface nitrogen groups devoid of any metal ion centers [46,47], it is now widely accepted that the transition-metal ion centers coordinated to four nitrogen groups (Me-N 4 ) on graphitic surfaces constitute the active site [22,23,30,48], whereas chelation primarily serves to prevent the metal center from passivation/corrosion under electrochemical conditions [49].…”
Section: Introductionmentioning
confidence: 99%
“…The high reduction current for both catalysts, especially for the MnPc/MWNT, was observed probably because of the generation of electrocatalytically active species, which usually form at temperatures from 700 to 950°C. Ladouceur et al have reported twice as high electrocatalytic activity of heat treated CoPc/XC-72, which was annealed at 800°C, compared to the non-pyrolysed CoPc/XC-72 [59,60].…”
Section: Rotating Disk Electrode Studies Of O 2 Reductionmentioning
confidence: 99%
“…The most active CoPc/C catalyst for ORR was obtained after pyrolysis at 600°C under an inert atmosphere for 2 h [94]. Detailed studies [95,96] showed that the SIMS intensities of Co ? and all other Co-containing organic fragments decreased with increasing pyrolysis temperature.…”
Section: Heat Treatmentmentioning
confidence: 99%